Question
upstudy study bank question image url

Find the derivative of the function \( T(x)=\tan \left(\frac{4 x+7}{5 x-4}\right) \)

Ask by Mann Guerrero. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The derivative of \( T(x) = \tan\left(\frac{4x + 7}{5x - 4}\right) \) is \( T′(x) = -\frac{51 \sec^2\left(\frac{4x + 7}{5x - 4}\right)}{(5x - 4)^2} \).

Solution

Let T(x) = tan((4x + 7)/(5x – 4)). To differentiate T(x), we first let   u(x) = (4x + 7)/(5x – 4). Since T(x) = tan(u(x)), by the chain rule we have:   T′(x) = sec²(u(x)) · u′(x). Now, we need to compute u′(x). Using the quotient rule for u(x) = N(x)/D(x) with N(x) = 4x + 7 and D(x) = 5x – 4, the quotient rule gives:   u′(x) = [N′(x)D(x) − N(x)D′(x)]/(D(x))². Differentiate N(x) and D(x):   N′(x) = 4 and D′(x) = 5. Substitute these into the quotient rule:   u′(x) = [4(5x – 4) − (4x + 7)(5)]/(5x – 4)². Expand and simplify the numerator:   4(5x – 4) = 20x – 16,   (4x + 7)(5) = 20x + 35. Thus, the numerator becomes:   20x – 16 − (20x + 35) = 20x – 16 – 20x – 35 = -51. So,   u′(x) = -51/(5x – 4)². Returning to T′(x):   T′(x) = sec²((4x + 7)/(5x – 4)) · (-51/(5x – 4)²). That is,   T′(x) = -51 sec²((4x + 7)/(5x – 4))/(5x – 4)². This is the derivative of T(x).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To find the derivative of the function \( T(x) = \tan\left(\frac{4x+7}{5x-4}\right) \), we will apply the chain rule and the quotient rule. 1. Let \( u = \frac{4x+7}{5x-4} \), then \( T(x) = \tan(u) \). 2. The derivative of \( \tan(u) \) is \( \sec^2(u) \cdot \frac{du}{dx} \). 3. Next, we need to find \( \frac{du}{dx} \) using the quotient rule: if \( u = \frac{f(x)}{g(x)} \), then \( \frac{du}{dx} = \frac{f'(x)g(x) - f(x)g'(x)}{(g(x))^2} \), where \( f(x) = 4x + 7 \) and \( g(x) = 5x - 4 \). Now we compute: - \( f'(x) = 4 \) - \( g'(x) = 5 \) Using the quotient rule: \[ \frac{du}{dx} = \frac{(4)(5x - 4) - (4x + 7)(5)}{(5x - 4)^2} \] Simplifying the numerator: \[ = \frac{20x - 16 - (20x + 35)}{(5x - 4)^2} \] \[ = \frac{20x - 16 - 20x - 35}{(5x - 4)^2} = \frac{-51}{(5x - 4)^2} \] Now, substituting \( u \) and \( \frac{du}{dx} \) back into the derivative of \( T(x) \): \[ T'(x) = \sec^2\left(\frac{4x + 7}{5x - 4}\right) \cdot \frac{-51}{(5x - 4)^2} \] Thus, the derivative of the function \( T(x) \) is: \[ T'(x) = -\frac{51 \sec^2\left(\frac{4x + 7}{5x - 4}\right)}{(5x - 4)^2} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy